The Effect of Carnitine Supplementation on Blood Ammonia Level in Epilepsy Children Treated with Valproic Acid: A Randomized Controlled Trial - I Gusti Lanang Sidiartha; I Gusti Ngurah Made Suwarba; Dyah Kanya Wati; Ida Bagus Subanada (Molecular and Cellular Biomedical Sciences, 2021)
Background: Long-term use of valproic acid is associated with a high level of blood ammonia related to carnitine deficiency. This study investigates the effect of carnitine supplementation on blood ammonia levels in children with epilepsy who have been treated with valproic acid for more than six months.Materials and Methods: This was a randomized, double-blind, placebo-controlled trial study where children with epilepsy who were treated with valproic acid were randomly allocated to the carnitine supplementation and control group. All children were followed for month, and then measured for blood ammonia level. Blood ammonia levels of both groups were compared using an Independent t-test with a significant of p<0.05.Results: Total of 32 children with epilepsy were enrolled as subjects in this study, with 16 children in carnitine group, and 16 children in control group. Among the subjects, 50% were male and 50% were female, with a mean age of 6.5 years old. The average duration of epilepsy in the carnitine and control group were 41.7 months and 36.9 months, respectively (p=0.419). The duration of valproic acid therapy in the carnitine and control group were 33.1 months and 27.6 months, respectively (p=0.483). The level of blood ammonia in carnitine and control group were 44.6 mg/dL and 81.4 mg/dL, respectively (p=0.007).Conclusion: The level of blood ammonia in a carnitine group was significantly lower than in a control group. It is recommended to give carnitine supplementation in epileptic children treating with long-term valproic acid.Keywords: ammonia, carnitine, epilepsy, seizure, valproic acid